Ekstrak Granul Nanopartikel Kulit Jeruk Sunkist (Citrus Sinensis (L.) Osbeck) Dan Ekstrak Kulit Jeruk Nipis (Citrus Aurantifolia) Terhadap Gambaran Perlemakan Hati Pada Tikus (Rattus Norvegicus) Model Diabetes) - Mutia, Maya Sari; Nabila, Putri; Hamsi, Ulpah Zahara; Lubis, Yolanda Eliza Putri (Universitas Prima Indonesia, 2024)
Sunkist oranges (Citrus sinensis (L.) Osbeck have a high content of anthocyanins (95% of which are cyanidin-3-glucoside and cyanidine-3-6